Ethnic concentration and language fluency of immigrants - Alexander M. Danzer; Firat Yaman (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2010)
The paper analyses the impact of regional own-ethnic concentration on the language proficiency of immigrants. It solves the endogeneity of immigrants' location choices by exploiting the fact that guest-workers in Germany after WWII were initially placed by firms and labor agencies. We find a robust negative effect of ethnic concentration on immigrants' language ability. Simulation results of a simultaneous location and learning choice model confirm the presence of the effect and show how immigrants with high learning cost select into ethnic enclaves. Under the counterfactual scenario of a regionally equal distribution of immigrants the share of German-speakers increases only modestly. – – Dieses Paper analysiert die Wirkung von regionalen ethnischen Konzentrationen auf die Sprachkompetenz von Einwanderern. Wir lösen die Endogenität der Wohnortentscheidungen der Einwanderer in dem wir den Umstand nutzen, dass Einwanderer im Rahmen der Gastarbeiteranwerbung ihren ersten Arbeitsort nicht auswählen konnten. Wir finden belastbare negative Effekte der ethnischen Konzentration auf die Beherrschung der deutschen Sprache. Simulationsergebnisse eines Modells mit gleichzeitigen Lern- und Wohnortentscheidungen unterstützen diesen Befund und zeigen, dass Einwanderer mit hohen Lernkosten gezielt in ethnische Enklaven ziehen. Unter dem Szenario einer Gleichverteilung der Einwanderer über Deutschland würde sich der Anteil der deutsch sprechenden Einwanderer nur geringfügig erhöhen.
Keywords: J61; R23; F22; 330; enclave; ethnic concentration; language proficiency; immigrants; instrumental variable; random utility mode; Migranten; Segregation; Ethnische Gruppe; Sprache; Mehrsprachigkeit; Deutsch; Deutschland